MONITORING ALAT PENGUKUR SUHU RUANG UNTUK PENYANDANG TUNANETRA DENGAN SISTEM KELUARAN SUARA BERBASIS MIKROKONTROLER ATMEGA328 - Trianawati, Yayuk; Yunginger, Raghel; Tansa, Salmawaty (Universitas Bina Taruna Gorontalo, 2023)
This research results in the design of a room temperature measuring device for the blind using the Atmega328 microcontroller. The design of the tool uses the Thermistor NTC 3950 temperature sensor. The sensor input is converted into a digital signal and processed by the Atmega 328 microcontroller using the Arduino Nano programming language. The results of measuring the temperature value of a classroom with an area of 6.8 x 5.5 m for the blind in SLB show that the temperature value is in the range of 26 – 29o. The accuracy of the instrument is measured by comparing a standard measuring instrument with a digital thermometer TPM-10. Observation of room temperature values was carried out for 10 hours in the reading range of values per 1 hour. From the results of a comparison with the standard digital thermometer TPM-10 measuring instrument, it shows that the accuracy of the tool is 98.35%.